Combining Multiple Types of Motor Rehabilitation Enhances Skilled Forelimb Use Following Experimental Traumatic Brain Injury in Rats. (November 2015) - Adkins, DeAnna L.; Ferguson, Lindsay; Lance, Steven; Pevtsov, Aleksandr; McDonough, Kevin; Stamschror, Justin; Jones, Theresa A.; Kozlowski, Dorothy A.
Background . Neuroplasticity and neurorehabilitation have been extensively studied in animal models of stroke to guide clinical rehabilitation of stroke patients. Similar studies focused on traumatic brain injury (TBI) are lacking. Objective . The current study was designed to examine the effects of individual and combined rehabilitative approaches, previously shown to be beneficial following stroke, in an animal model of moderate/severe TBI, the controlled cortical impact (CCI). Methods . Rats received a unilateral CCI, followed by reach training, voluntary exercise, or unimpaired forelimb constraint, alone or in combination. Forelimb function was assessed at different time points post-CCI by tests of skilled reaching, motor coordination, and asymmetrical limb use. Results . Following CCI, skilled reaching and motor coordination were significantly enhanced by combinations of rehabilitation strategies, not by individual approaches. The return of symmetrical limb use benefited from forelimb constraint alone. None of the rehabilitation strategies affected the size of injury, suggesting that enhanced behavioral function was not a result of neuroprotection. Conclusions . The current study has provided evidence that individual rehabilitation strategies shown to be beneficial in animal models of stroke are not similarly sufficient to enhance behavioral outcome in a model of TBI. Motor rehabilitation strategies for TBI patients may need to be more intense and varied. Future basic science studies exploring the underlying mechanisms of combined rehabilitation approaches in TBI as well as clinical studies comparing rehabilitation approaches for stroke versus TBI would prove fruitful.